Local biocompatibility and biochemical profile of hepatic cytolysis in subcutaneous implantation of polylactide matrices - E. A. Ivanova; A. N. Dzyuman; M. V. Dvornichenko (Бюллетень сибирской медицины)
The aim of the study was to investigate local biocompatibility and systemic effects of nonwoven polylactide (PLA) matrices on blood and liver parameters after their subcutaneous implantation in Wistar rats.Materials and methods. Bioabsorbable fibrous PLA matrices were produced by electrospinning and had dimensions (10 × 10 mm², thickness of no more than 0.5 mm; fiber diameter in the matrix ~1 μm) appropriate for subcutaneous implantation in white laboratory rats. Polymer implants were sterilized in ethylene oxide vapor. Thirty days after the implantation of PLA matrices, local biocompatibility according to GOST ISO 10993-6-2011, cellular parameters (total leukocyte count, hemogram, erythrocyte count, hemoglobin concentration), and biochemical blood parameters (lactate concentration, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels) were studied, and a standard histologic evaluation of the liver was performed.Results. PLA matrix samples were mild local irritants on a scale of 1–1.9 points according to GOST ISO 10993-6-2011 criteria 30 days after the subcutaneous implantation. The median density of distribution of multinucleated giant cells (MNGCs) in the connective tissue around and in PLA matrices was 1,500 (1,350; 1,550) per 1 mm² of a slice. Pronounced leukocytic reaction due to lymphocytosis was noted (an increase by 1.7 times compared with a sham-operated (SO) control group, р < 0.02). The absence of a significant neutrophil count in the blood revealed sterile inflammation proceeding in the subcutaneous tissue around the PLA materials. Normalization of hepatic cytolysis markers (ALT and AST activity) in the blood without pronounced changes in the structure of the liver and the number of binuclear hepatocytes was noted. These markers were increased in SO controls (ALT up to 123% and AST up to 142%, p < 0.001 compared with values in the intact group).Conclusion. Nonwoven PLA matrices are biocompatible with subcutaneous tissue, undergo bioresorption by MNGCs, and have a distant protective effect on the functional state of the liver in laboratory animals. Hypotheses on the detected systemic effect during subcutaneous implantation of PLA matrices were discussed; however, specific mechanisms require further study.